EduTech Acceleration: Strengthening Teacher Competencies through AI-Based Learning Media Training - Dewi Fatmarani Surianto; Muhammad Fajar B; Ayu Hasnining; Andi Akram Nur Risal; Haekal Febriansyah Ramadhan; Dewi Fatmawati Surianto (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
The rapid adoption of Generative Artificial Intelligence (GenAI) in education requires teachers to strengthen their competencies in producing accurate, ethical, and safe learning media. This community engagement program was conducted in a secondary education institution to enhance teachers’ AI literacy and ability to apply structured prompting using the CRISP-EDU framework. The training emphasized fact-checking, credible source attribution, bias mitigation, and student data protection principles. Evaluation results demonstrate improvements across all competency dimensions: understanding of CRISP-EDU fundamentals (+42%), AI licensing and ethics (+32%), classroom AI-related standard operating procedures and risk awareness (+26%), generative AI utilization (+15%), and practical application of CRISP-EDU (+23.66%). These findings indicate a shift in teachers’ roles from passive users to critical and ethical content curators capable of producing safe and contextually appropriate AI-based learning materials.